Awakening Self Awareness to Strengthen Health Protocol Discipline - Subiyanto, Didik; Prayekti, Prayekti; Septyarini, Epsilandri (LPPM Universitas Bina Bangsa, 2022)
Background: The high transmission of COVID-19 in Indonesia requires serious handling. The public is also required to be involved in preventing the transmission of Covid-19, through discipline in carrying out health protocols. From the beginning of 2020 until the middle of 2021, the COVID-19 outbreak has claimed many lives and severely hampered human activities in many sectors. The economic and education sectors have felt the negative impact of the COVID-19 outbreak, so it is necessary to conduct research related to strategic prevention efforts. Objective: The purpose of this study was to determine the factors that can improve the discipline of health protocols, through efforts to increase the self-awareness of the younger generation, especially among students. Methods: Samples were taken from the student population of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa (UST) as many as 148 samples. Meanwhile, to get the data we used a questionnaire distributed online. Furthermore, Structural Equation Modeling (SEM) was used to analyze the proposed hypothesis. Results: Social Capital and Perception of Information Disclosure positively affect Self-Awareness. Self-Awareness has a positive effect on the Health Protocol Discipline. Meanwhile, Social Capital and Perception of Information Disclosure do not directly affect the Health Protocol Discipline. Level of Readiness: In particular, research results become strategic inputs related to government policies to create protocol discipline, especially among students. Meanwhile, in general, our research tries to provide a research model in the form of the Empirical Research Model (ERM), which is a strategic mindset in finding the right policy footing, in critical situations